On national incom - C. GINI (PSL Quarterly Review, 2014)
The article discusses national income as it presents itself in pathological periods, and as seen more especially in the light of post-war experiences. From the statistical-theoretical angle where practical interests and economic inquiries converge and bring into focus the real problems of income, consumption, savings, investments, and their mutual relations, we find that even the most subtle premises of methodology need to be studied when framing plans for solving the problems of present day reconstruction and taxation. English-speaking students of such questions will note with interest the references the author makes to Pigou’s recent work on “Income” and the restatement of the opinions the author himself had occasion to sustain before the Royal Statistical Society in London in 1939.